THE FAMILY LEARNING APPROACH: A CONCEPT NOTE - Dumond, Marine (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2019)
The family learning approach, home education, or homeschooling is an alternative pedagogical choice that enables parents to take charge of their school-aged child’s education by replacing full-time school attendance. Scientific research on the family learning approach is emerging and mainly conducted and published in English-speaking contexts. This article presents a brief concept note of recent and international scientific literature on the family learning approach in order to identify studied dimensions and current knowledge. The following themes are addressed: history, current picture, place in society, and issues of the family learning approach.